Variasi dan Kronologi Bentuk Logo Kamer VOC pada Meriam Kuno: Perbandingan pada Koleksi Mueum-Museum di Jawa, Malaysia, dan Australia - Panji Syofiadisna; Yuka Nurtanti Cahyaningtyas; Dimas Nugroho; Harriyadi; Dewangga Eka Mahardian; Indah Permatasarie Tjan; Eny Nurhayati (AMERTA, 2025)
Abstract, VOC Chamber Logo on Ancient Cannons, the identity in Spice Route. Vereenigde Oost-Indische Compagnie (VOC) as a giant company over a periode of two centuries has six trade chambers across continental business activities as a trading company. The six chambers are in Amsterdam, Zeeland, Hoorn, Delft, Enkhuizen, and Rotterdam. The chamber logos found were not in the same shape but had variations in shape and attribute. There is even a chamber that has a different logo at certain times. This variation can be considered as visual communication. The problem raised in this article is to reveal the variations of the VOC trade chambers logo from both iron and bronze cannons and try to explain the comparison of each logo variation. This article aims to provide an initial overview of the study of ancient VOC cannons, especially during the VOC era in Indonesia. The data collections was conducted observation techniques of ancient cannon that feature the VOC chamber logo at the Jakarta Historical Museum, Bahari Museum, Mpu Tantular Museum, Vredeburg Museum, Cakraningrat Museum, Western Australia Musueum, and few States of Malaysia Kingdom. The next step is to process the data for classification and typology. The presence of these six logos serves as both an identity and evidence that the chamber’s role was crucial in VOC activities in the archipelago during that time. Keywords: Trade chamber, logo, ancient cannon, Vereenigde Oost-Indische Compagnie (VOC)   Abstrak, VOC sebagai perusahaan raksasa dalam kurun waktu dua abad memiliki enam logo kamer dagang dalam kegiatan perniagaan lintas benua. Enam kamer tersebut adalah Amsterdam, Zeeland, Hoorn, Delft, Enkhuizen, dan Rotterdam. Logo kamer yang ditemukan ternyata tidak dalam bentuk yang sama namun ada variasi bentuk. Bahkan ada kamer yang memiliki logo yang berbeda dalam kurun waktu tertentu. Variasi ini dapat dianggap sebagai identitas visual. Persoalan yang disajikan dalam tulisan ini adalah mengungkap variasi logo kamer VOC baik dari meriam besi maupun meriam perunggu serta menjelaskan perbandingan dari setiap variasi logo. Tujuan dari tulisan ini memberikan rona awal dari kajian meriam kuno, terutama pada masa VOC di Indonesia. Pengumpulan data yang dilakukan dengan teknik observasi (pengamatan) terhadap meriam kuno yang memiliki logo kamer VOC di Museum Sejarah Jakarta, Museum Bahari, Museum Mpu Tantular, Museum Vredeburg, Museum Cakraningrat, Museum Western Australia, dan beberapa negara bagian Malaysia. Selanjutnya adalah melakukan pengolahan data untuk klasifikasi dan tipologi. Keberadaan enam logo ini menjadi identitas dan bukti bahwa peran kamer sangat krusial dalam aktifitas VOC di Nusantara kala itu.    Kata kunci: Kamer, logo, meriam kuno, Vereenigde Oost-Indische Compagnie (VOC)